2014
DOI: 10.1553/populationyearbook2013s185
|View full text |Cite
|
Sign up to set email alerts
|

The longevity of academicians: evidence from the Saxonian Academy of Sciences and Humanities in Leipzig

Abstract: This study addresses the mortality of the members of the Saxonian Academy of Sciences and Humanities in Leipzig. In fact, learned societies have been shown to present vanguard groups in the achievement of longevity. We use biographical records from the members of the Saxonian Academy of Sciences from 1846 to 2010 and compare their mortality to German life table estimates, where particularly attention is paid to the mortality differentials between eastern and western Germany. The Saxonian academicians show inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(45 reference statements)
0
4
0
1
Order By: Relevance
“…Associations of prominent scientists represent another type of small group with exceptional longevity. For example, members of the Royal Society in the UK and of the national academies of sciences in Austria, Germany, and Russia have been shown to have unusually long life spans [15][16][17] . These individuals, who are predominantly men, may differ from the rest of the population not only in terms of their intellectual capacity, but also because they tend to have a healthier and more rational lifestyle, a somewhat higher income, and a childhood characterized by better health and living conditions, which would have fostered educational achievement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Associations of prominent scientists represent another type of small group with exceptional longevity. For example, members of the Royal Society in the UK and of the national academies of sciences in Austria, Germany, and Russia have been shown to have unusually long life spans [15][16][17] . These individuals, who are predominantly men, may differ from the rest of the population not only in terms of their intellectual capacity, but also because they tend to have a healthier and more rational lifestyle, a somewhat higher income, and a childhood characterized by better health and living conditions, which would have fostered educational achievement.…”
mentioning
confidence: 99%
“…These individuals, who are predominantly men, may differ from the rest of the population not only in terms of their intellectual capacity, but also because they tend to have a healthier and more rational lifestyle, a somewhat higher income, and a childhood characterized by better health and living conditions, which would have fostered educational achievement. The progress in mortality reductions among these scientific elites has been faster than the corresponding national averages, even though these groups initially had record-low mortality levels [17] .…”
mentioning
confidence: 99%
“…Indeed, the academicians' life expectancy at age 50 of around twenty years ago has still not been reached by the Austrian total population of today. It has been suggested that the exceptional longevity is not only the result of selectivity into election to membership of academicians (for an extensive discussion see Andreev et al 2011;Winkler-Dworak and Kaden 2013). According to the literature on the social gradient in mortality (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…What is even more striking is that only very recently average Austrian men have reached a life expectancy value at age 50 similar to that which academicians already enjoyed around 1980. Therefore, several authors concluded that academicians indeed represent a vanguard group in the achievement of longevity (Andreev et al 2011;Winkler-Dworak and Kaden 2013), and thus, academies age more rapidly than other population groups or general populations. However, in addition to the exceptionally high and increasing longevity, many European academies have experienced an upward secular trend in the mean age at election contributing to the ageing of academies via the inflow (Riosmena et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Neben den bereits genannten auf der Familienrekonstitution basierenden Werken sind dies insbesondere Publikationen, die spezifische Teilbevölkerungen untersuchen. Mit einem Fokus auf Kardinäle [ 10 ], Wissenschaftler [ 11 , 12 ] oder Mediziner [ 13 ] ist eine Untersuchung der geschlechtsspezifischen differenziellen Mortalität dabei häufig aufgrund der geringen Fallzahlen bei Frauen nicht möglich. In ihren Untersuchungen zu berühmten Persönlichkeiten können de la Croix und Licandro die Geschlechterdimension zwar berücksichtigen, müssen das Geschlecht aber über Vornamen approximieren.…”
Section: Introductionunclassified